Seleção de scfv (single-chain variable fragment) contra proteínas totais de Strongyloides venezuelensis por Phage Display e sua aplicação na detecção sorológica de imunocomplexo na estrongiloidíase humana - Levenhagen, Marcelo Arantes (2014)
Strongyloidiasis is a helminthiasis of neglected condition that has no gold standard of parasitological diagnosis due to the intermittent release of larvae in feces. The maintenance of the parasite in the host can lead to chronicity and hyperinfection. Recombinant antibody fragments (single-chain fragment variable, scFv) have been used in the development of more effective methods of diagnosis. The aim of this study was to obtain scFv by Phage Display, from a combinatorial library, against total proteins of Strongyloides venezuelensis, for its further application in the serological diagnosis of human strongyloidiasis by immune complexes detection. After two cycles of selection, the scFv clones that reacted against the total proteins of the parasite were characterized by sequencing. To characterize the antigenic component of the total extract in which the scFv molecule bound, the pull-down assay, immunofluorescence antibody test (IFAT) and mass spectrometry (CID-MS/MS) were performed. The ability of scFv to detect the immune complexes was verified by enzyme-linked immunosorbent assay (ELISA), flow cytometry using magnetic beads and surface plasmon resonance (SPR), using serum pool of individuals positive for strongyloidiasis, positive for other parasites and healthy. It was performed the sandwich ELISA using scFv for detecting immune complexes in 124 serum samples from individuals: 40 positive for strongyloidiasis; 44 positive for other parasitic diseases and 40 healthy. The diagnostic accuracy of this method was determined by the data of the ROC curve. Of the 96 clones, 4 (A4, B4, H2 and H3) reacted against total proteins of the parasite and sequencing analysis showed that the four clones had the same deduced amino acid sequence. The 15% SDS-PAGE, after pull-down assay, demonstrated that the scFv was able to bind to an antigenic fraction of ~65kDa from S. venezuelensis, present in the body and digestive system of infective larvae (L3), as verified by IFAT. The results obtained by CID-MS/MS and bioinformatics analysis showed that this antigenic fraction presents high similarity with heat shock protein (HSP60) of Strongyloides sp., an important protein involved in host-parasite relationship. The ELISA, flow cytometry and SPR methods demonstrated the ability of scFv to detect immune complexes in pool of sera from individuals with strongyloidiasis and differentiate from the pool of sera from individuals with other parasitic diseases and healthy. The sandwich ELISA with 124 serum samples showed high diagnostic accuracy with 97.50% sensitivity, 98.81% specificity, area under the curve of 0.9993 and likelihood ratio of 81.90. In this study, success was obtained in the selection and characterization of a scFv that binds to a specific antigenic fraction of the parasite and that proved to be innovative and effective in the diagnosis of human strongyloidiasis.